Effects of tractor ownership on agricultural returns-to-scale in household maize production: Evidence from Ghana - Takeshima, Hiroyuki; Houssou, Nazaire; Diao, Xinshen (International Food Policy Research Institute, 2017)
The rise in returns-to-scale (RTS) has often been an integral part of the agricultural transformation process around the world. Although tractor ownership is often associated with greater RTS in agriculture, whether tractor ownership actually causes such increase in RTS has not been formally tested in the literature. We provide evidence that partly bridges this knowledge gap, using unique survey data of tractor-owning farm households in Ghana. We find that owning tractors significantly increases RTS in maize production from the households’ largest monocropped plot. Specifically, owning tractors raises RTS for farmers because they can till greater areas, even though returns from tilling more land remain relatively unaffected. The increase in RTS holds regardless of the values of tractors owned. These sets of evidence are obtained by addressing jointly the multiple sources of endogeneity of tractor ownership, tractor values, tillage intensity, and other inputs used, through combinations of inverse-probability weighing method, generalized method of moments method, and the mediation effects model with multiple mediators. The adoptions of mechanical technologies (tractors) and their ownerships are causing, rather than simply responding to, the rise in RTS in Ghanaian maize production.